ANALISIS MIKROBIOLOGI SIRUP BUAH PEDADA (sonneratia caseolaris) DIKABUPATEN KETAPANG - Marisa Nopriyanti; Trian Adimarta; Lisa Sapitri (Pengelola Jurnal Politeknik Negeri Ketapang, 2023)
This study aims to determine the boiling process in the manufacture of broiler syrup using the unblender method, to determine the heating process in the preparation of broiler syrup using the blended method and to determine the APM/ml of Coliform and E.coli contamination in broiler syrup. The process of making pedada fruit syrup (Sonneratia caseolaris) includes two methods, namely without blending and blending. The pedada fruit with the method without blending, namely the pedada fruit that has been cleaned and cut into pieces, then added 65% sugar and 1000 ml of water and then boiled, while the blended method of pedada is mashed and added 1000 ml of water then filtered to extract the juice, after that added 65 % sugar. The syrup is heated for ± 30 minutes with a stove temperature of ± 100°C, that is, by stirring it until it thickens slightly, then cools it and puts it in a bottle. This research method uses the MPN method using lactose broth media. The results of the analysis of contamination of Coliform bacteria and E.coli syrup of breast milk (Sonneratia caseolaris) were carried out using two processes and the method of broiler fruit with the boiling process and the non-blender method and the heating process in the blender method. Analysis of Coliform contamination used series 3, namely using 3 tubes for each dilution, after incubation for 24 hours each series was negative, there were no bubbles and gas. Analysis of E.coli contamination used 6 tubes, after incubation for 24 hours each tube was negative for no bubbles and no gas.